Predicting Drug Metabolism Induction In Silico - Schuster, Daniela; Steindl, Theodora M.; Langer, Thierry (Current Topics in Medicinal Chemistry, 2006)
The inducibility of drug-metabolizing enzymes and transporters by numerous xenobiotics has become a vital issue to be considered in the drug development process. Activation of so-called orphan nuclear receptors has been identified to result in increased expression of these detoxifying systems and consequently altered drug levels in the human body. In order to anticipate such mechanisms already in early stages of drug design and to avoid dangerous drug-drug interactions, reliable in silico simulation tools are highly desirable. This review aims to give an introduction into induction of drug metabolism and transport and focuses on computer-assisted molecular modeling prediction techniques, on their applicability and limitations, on recent case studies, and on success stories.
Keywords: Nuclear receptors